Zooplankton di Perairan Teluk Doreri, Kabupaten Manokwari, Provinsi Papua Barat - Alfret Roni Marani; Alianto Alianto; Vera Sabariah; Marhan Manaf; Tresia Sonya Tururaja; Safar Dody (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTThis study aims to determine the abundance and composition of zooplankton in the waters of Doreri Bay. Water samples were taken at a depth of 5 meters and 10 meters at 2 research stations. Identification of zooplankton was carried out using the sweep method. The results obtained that the average abundance of zooplankton at station 1 at a depth of 5 and 10 meters respectively was 54 ind/L in the morning and 33 ind/L in the afternoon and 33 ind/L in the morning and 30 ind/L in the afternoon. On the other hand, the average abundance of zooplankton at station 2 at a depth of 5 meters and 10 meters consecutively was 61 ind/L in the morning and 67 ind/L in the afternoon and 81 ind/L in the morning and 66 ind/L in the afternoon. The number of zooplankton genera is 29 genera with a percentage of 32.41% in 1 genera (Nauplius sp.), 20.99% in 1 genera (Calanus sp.), 5-9% in 2 genera (Epiplocylis sp., and Euntintinnus sp.), 3-.5% in 3 genera (Arcelia sp., Rhabdonella sp., and Salpingella sp.), and 0-3% in 22 genera (Abarenicola sp., Amphorellopsis sp., Ascomorpha sp., Balanus sp., Codonellopsis sp., Cornutella sp., Cyphoderia sp., Evadne sp., Lecane sp., Lithotrobus sp., Notholca sp., Oikopleura sp., Paravafella sp., Penaeus sp., Pinctada sp., Pleuraspis sp., Protorhabdonella sp., Spiophanes sp., Tintinnidium sp., Tintinnopsis sp.,Trichocerca sp., and Undella sp.). Keywords: Abundance, compositon, zooplankton, Doreri Bay Penelitian ini bertujuan untuk mengetahui kelimpahan dan komposisi zooplankton di perairan Teluk Doreri. Sampel air diambil pada kdalaman 5 meter dan 10 meter pada 2 stasiun penelitian. Identifikasi zooplankton dilakukan dengan menggunakan metode penyapuan. Hasil yang diperoleh rata-rata kelimpahan zooplankton di stasiun 1 pada kedalaman 5 dan 10 meter secara berturut-turut sebesar 54 ind/L pada pagi hari dan 33 ind/L di sore hari serta 33 ind/L di pagi hari dan 30 ind/L di sore hari. Rata-rata kelimpahan zooplankton di stasiun 2 pada kedalaman 5 meter dan 10 meter secara berturut-turut sebesar 61 ind/L di pagi hari dan 67 ind/L di sore hari serta 81 ind/L di pagi hari dan 66 ind/L di sore hari. Jumlah genera zooplankton adalah 29 genera dengan persentase 32,41% sebanyak 1 genera (Nauplius sp.), 20,99% sebanyak 1 genera (Calanus sp.), 5-9% sebanyak 2 genera (Epiplocylis sp., dan Euntintinnus sp.), 3-5% sebanyak 3 genera (Arcelia sp., Rhabdonella sp., dan Salpingella sp.), dan 0-3% sebanyak 22 genera (Abarenicola sp., Amphorellopsis sp., Ascomorpha sp., Balanus sp., Codonellopsis sp., Cornutella sp., Cyphoderia sp., Evadne sp., Lecane sp., Lithotrobus sp., Notholca sp., Oikopleura sp., Paravafella sp., Penaeus sp., Pinctada sp., Pleuraspis sp., Protorhabdonella sp., Spiophanes sp., Tintinnidium sp., Tintinnopsis sp.,Trichocerca sp., dan Undella sp.).Kata kunci: Kelimpahan, komposisi, zooplankton, Teluk Doreri